2009
DOI: 10.1002/app.30726
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of novel organosoluble polyesters based on a DIOL with azaquinoxaline ring

Abstract: A series of new polyesters were synthesized by polycondensation of aliphatic and aromatic dicarboxylic dichlorides with a novel quinoxaline diol, 2,3-bis (4-hydroxy phenyl)-5-azaquinoxaline (DIOL). The DIOL was synthesized by reacting 4,4 0 -dihydroxy benzil with 2, 3-diaminopyridine (yield: 85%), and characterized by FTIR and 1 H-NMR spectra. All polyesters showed good solubility in most aprotic polar solvents such as NMP (Nmethylpyrrolidone), DMF (dimethylformamide), DMSO (dimethylsulfoxide), DMAc (dimethyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…DSC studies of some polyamides [11,12] were reported in literature. We successfully prepared aromatic polyamides [13] , polyimides [14] , polyesters, polyquinoxalines, from a number of new functional monomers [15] . Thermally stable polymers have received extensive interest due to the increasing demands for high temperature polymers as replacements for ceramics and metals in the automotive, aerospace, and microelectronics industries.…”
Section: Introductionmentioning
confidence: 99%
“…DSC studies of some polyamides [11,12] were reported in literature. We successfully prepared aromatic polyamides [13] , polyimides [14] , polyesters, polyquinoxalines, from a number of new functional monomers [15] . Thermally stable polymers have received extensive interest due to the increasing demands for high temperature polymers as replacements for ceramics and metals in the automotive, aerospace, and microelectronics industries.…”
Section: Introductionmentioning
confidence: 99%